Review of The Importance of Being Iceland: Travel Essays in Art - Morrell, Amish (C The Visual Arts Foundation, 2009)
Eileen Myles begins The Importance of Being Iceland with an account of being invited by curator Hans Ulrich Obrist to participate in the exhibition Do it, held in Reykjavik in 1996. As she explains, she came to know Obrist through a mutual interest in the 19th century Swiss writer Robert Walser, whose writing often described what he saw while on long walks. Walser, who sometimes undertook these excursions at night, wrote in microscopic script, and in his written descriptions abandoned himself to his surroundings in a way that gave equal attention to the most spectacular and the most ordinary of details. This practice, a form of literary modernism that combined elements of popular fiction, literature, and personal reflection, sets the stage for The Importance of Being Iceland. Through her own peripatetic method, Myles brings together ideas and experiences from vastly disparate realms, describing them in ways that shifts the reader's sense of their scale and significance.